Placement of former english language learners in middle schools: general education or dual language?. Issue 4 (21st April 2021) - Torff, Bruce; Murphy, Audrey Figueroa
ABSTRACT: Historically, many educators have attempted to help English Language Learners (ELLs) develop sufficient English skills to be reclassified so that they can be placed in general-education classrooms. At present, educators increasingly favor a policy of placing former ELLs in dual-language settings. But it remains unclear whether former ELLs in middle schools perform better academically in general-education (GE) or dual-language (DL) classrooms. Research was conducted to compare former ELLs placed in GE settings and those who remained in DL classrooms on state tests in English Language Arts (ELA) and math ( n = 99) at the middle-school level. In both subjects, DL students outperformed GE students on two of four yearly test administrations following reclassification, and for ELA averaged across the four, with single-test effects stronger in math than ELA. GE students did not outperform DL students on any of eight tests. Calling into question policies favoring placement of former ELLs in GE classes, the results underscore the efficacy of continuing to use students' home language in instruction following reclassification.